DEVELOPMENT OF CROSSWORD-BASED STUDENT WORKSHEETS (LKS) FOR GRADE IV STUDENTS OF STATE ELEMENTARY SCHOOL 02 AIR BELITI SUNGAI PERIGI ON THE BEAUTY OF TOGETHERNESS THEME - Ani Ariska; Rudi Erwandi; Tio Gusti Satria (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aims to develop a product in the form of Crossword-based Thematic Student Worksheets on the theme 1 The Beauty of Togetherness in class IV SDN 02 AB.S PERIGI in accordance with the 2013 curriculum and to produce valid and practical worksheets for use in learning. This research is a development research with 4D (Define), (Design), (Develop), (Disseminate) models. Based on the results of the research analysis by the three experts, namely: linguists, material experts and media experts overall, it shows that the Crossword-based Thematic LKS on theme 1 The Beauty of Togetherness in class IV SDN has met the valid criteria with a percentage of 98.77%. Categorized as